2013
DOI: 10.5507/bp.2011.059
|View full text |Cite
|
Sign up to set email alerts
|

A significant proportion of patients with chronic myeloid leukemia and suboptimal response according to European Leukemia Net criteria have excellent prognosis without treatment change

Abstract: Background. The Recommendations of the European Leukemia Net (ELN) have become an essential tool in the management and prognosis of patients with chronic myeloid leukemia (CML) treated with tyrosine kinase inhibitors (TKIs). However, the definition of suboptimal response remains under discussion. Methods. We used conventional cytogenetics for the detection of clonal changes in Ph-positive and negative clones. RT-PCR and sequencing were carried out on peripheral blood leukocytes to detect the type of BCR-ABL1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, monitoring of additional changes such as ACAs is useful for identifying patients at higher risk of treatment failure (Oehler, 2013). Definition of CML according to hematologic, cytogenetic, and molecular changes can be useful in predicting treatment responses and in organizing guidelines for CML treatment, especially in the chronic phase (Rohon et al, 2013).…”
Section: Role Of Acas In Prognosis and Treatment Responsementioning
confidence: 99%
“…Therefore, monitoring of additional changes such as ACAs is useful for identifying patients at higher risk of treatment failure (Oehler, 2013). Definition of CML according to hematologic, cytogenetic, and molecular changes can be useful in predicting treatment responses and in organizing guidelines for CML treatment, especially in the chronic phase (Rohon et al, 2013).…”
Section: Role Of Acas In Prognosis and Treatment Responsementioning
confidence: 99%
“…Mainly because of the need for more evidence, especially for an early treatment change, ELN recommended patients with warning signs to be monitored more stringently given the assumption that they would achieve an inadequate treatment response and consequently result in a poor outcome [2]. This has motivated several investigators to conduct studies challenging the validity of the ELN recommendations, and Rohon et al [4] tested the clinical significance of suboptimal response according to the 2009 ELN recommendations in a retrospective analysis, which included 110 patients with both early and late CML-CP. Although the number of patients in that study was relatively small, the authors showed that patients with optimal and suboptimal responses had similar outcomes, and all patients with suboptimal response eventually achieved complete CyR (CCyR) if they were kept on receiving imatinib.…”
mentioning
confidence: 99%
“…Although the number of patients in that study was relatively small, the authors showed that patients with optimal and suboptimal responses had similar outcomes, and all patients with suboptimal response eventually achieved complete CyR (CCyR) if they were kept on receiving imatinib. Furthermore, they stated that patients with suboptimal response clearly form a heterogeneous group of which a significant proportion show characteristics that correspond to patients with optimal response [4].…”
mentioning
confidence: 99%